Combining ambulatory and laboratory assessment of rollator use for balance and mobility in neurologic rehabilitation in-patients. (September 2015) - Tung, James Y.; Chee, Justin N.; Zabjek, Karl F.; McIlroy, William E.
Abstract Purpose: Despite the common use of rollators (four-wheeled walkers), understanding their effects on gait and balance is limited to laboratory testing rather than everyday use. This study evaluated the utility of an ambulatory assessment approach to examine balance and mobility in everyday conditions compared to a laboratory assessment. Methods: Standing and walking with a rollator was assessed in three neurological rehabilitation in-patients under two conditions: (1) in laboratory (i.e. forceplate, GaitRite), and (2) while performing a natural walking course within and outside of the institution. An instrumented rollator (iWalker) was used to measure variables related to the balance control (e.g. upper limb kinetics), destabilizing events (e.g. stumbling), and environmental context. Results: Two of three patients demonstrated greater reliance on the rollator for standing balance (2.3–5.9 times higher vertical loading, 72–206% increase in COP excursion) and 29–42% faster gait during the walking course compared to the laboratory. Importantly, destabilizing events (collisions, stumbling) were recorded during the walking course. Such events were not observed in the laboratory. Conclusion: This study illustrated a greater reliance on the rollator during challenges in everyday use compared to laboratory assessment and provided evidence of specific circumstances associated with destabilizing events that may precipitate falls in non-laboratory settings. Implications for Rehabilitation The value of combining laboratory and ambulatory assessment approaches to provide a more comprehensive profile of the risks and benefits of rollator use to prevent falling was studied. Patients demonstrated greater reliance on rollator assistive devices for standing balance and exhibited higher gait speeds during ambulatory assessment, compared to standard laboratory protocols. Repeated instances of events that may precipitate falls (e.g. collisions, stumbling, and unloading behaviors) were observed only during the ambulatory assessment. Individual challenges to balance can be used to identify specific training targets, assess suitability for assistive devices, and recommend rehabilitation goals.